Flood risk discounts in the Danish housing market - Giorgio Mirone; Johannes Pöschl (Danmarks Nationalbank, 2021)
We investigate the effects of the risk of flooding on the prices of single-family homes in Denmark. Houses that are exposed to flood risk today, as well as houses that will be exposed to flood risk in the future due to rising sea levels, are priced at a discount.
Keywords: 330; Climate; household balance sheets; Housing finance